2012
DOI: 10.2174/138161212802002625
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier Integrity and Glial Support: Mechanisms that can be Targeted for Novel Therapeutic Approaches in Stroke

Abstract: The blood-brain barrier (BBB) is a critical regulator of CNS homeostasis. Additionally, the BBB is the most significant obstacle to effective CNS drug delivery. It possesses specific charcteristics (i.e., tight junction protein complexes, influx and efflux transporters) that control permeation of circulating solutes including therapeutic agents. In order to form this “barrier,” brain microvascular endothelial cells require support of adjacent astrocytes and microglia. This intricate relationship also occurs be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
123
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 335 publications
(434 reference statements)
0
123
0
1
Order By: Relevance
“…Our investigation revealed that bystander microglia exposed to overlays from infected astrocytes produce significantly more IL-1α, IL-1β, IL-6, and IL-8 as compared to the directly infected cells. These pro-inflammatory cytokines are strongly linked with BBB damage, which indicates that BBB permeability may be the result of bystander cell inflammation rather than direct infected cells [4749]. This cytokine induction recapitulates in our primary cell model and occurs as early as 1 hour post infection, which underscores the need for an effective therapeutic that can mitigate this massive pro-inflammatory cytokine response.…”
Section: Discussionmentioning
confidence: 67%
“…Our investigation revealed that bystander microglia exposed to overlays from infected astrocytes produce significantly more IL-1α, IL-1β, IL-6, and IL-8 as compared to the directly infected cells. These pro-inflammatory cytokines are strongly linked with BBB damage, which indicates that BBB permeability may be the result of bystander cell inflammation rather than direct infected cells [4749]. This cytokine induction recapitulates in our primary cell model and occurs as early as 1 hour post infection, which underscores the need for an effective therapeutic that can mitigate this massive pro-inflammatory cytokine response.…”
Section: Discussionmentioning
confidence: 67%
“…Additionally, matrix proteins have been shown to influence the expression of TJ proteins, such as occludin, suggesting that the extracellular matrix plays a role in maintaining TJ protein integrity. 15,26,30 Astrocytes Astrocytes are the most abundant cell type in the brain and display a fibroblast-like morphology within grey matter 15,31 ; however, this morphology can be influenced by their CNS location and associations with other cell types that are in close proximity. 32 Astrocyte end-feet cover over 99% of cerebral capillaries, 33 leading to critical cell-cell interactions that directly modulate and regulate BBB characteristics.…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…A központi idegrendszerben legfontosabb szerepet ját-szó P-gp transzporter szerepét Murozono és mtsai mdr1 knockout egereken tanulmányozták. Kísérleteik alapján az mdr1 génnel nem rendelkező állatokon sokkal kisebb volt az infarktus térfogata középagyi artéria okklúzióját követően [47,48], mint a vad típusú egereken. Farmakológiai megközelítésben pedig a P-gp inhibitor cyclosporin A alkalmazása drámaian csökkentette az infarktus nagyságát stroke-os állatokon [49].…”
Section: Strokeunclassified